Institutionalizing intersectionality : the changing nature of European equality regimes - Krizsán, Andrea; Skjeie, Hege; Squires, Judith (Gender and politics (Palgrave Macmillan (Firm)), 2012)
What is the relative importance of different inequalities for policymaking? Should they all be protected similarly, or are some different and deserving of wider protection? Does the widening protection of multiple inequalities open up the potential for addressing their intersections as well, or is more specific attention needed if intersectionality is to be addressed by equality institutions? The current European arena provides a laboratory for comparative research about these questions. The last decade has seen a steady move away from policy approaches that address different inequalities separately and a move towards an integrated approach to multiple inequalities. This collection maps the ways in which multiple inequalities are being addressed institutionally in Europe, and identifies the changing patterns of institutionalization. Using country-based and region-specific case studies it offers a comparative analysis of the multidimensional equality regimes that are emerging in Europe, and analyses the potential that these have for 'institutionalizing intersectionality'.